Predictors of very early postpartum weight loss in women with recent gestational diabetes mellitus. (2nd January 2020) - Nicklas, Jacinda M.; Zera, Chloe A.; Seely, Ellen W.
Abstract: Objective: Women with gestational diabetes (GDM) have a 7–12-fold increased risk for developing type 2 diabetes later in life. Postpartum weight retention is highly predictive for future obesity, and further increases risk for type 2 diabetes. We sought to identify predictors of losing at least 75% of gestational weight gain by very early postpartum in women with recent GDM. Methods: We recruited women with GDM during pregnancy or just after delivery. Prepregnancy weight was self-reported at recruitment; gestational weight gain, mode of delivery, and insulin use were extracted from medical records. At a mean of 7.2 (±2.1) weeks postpartum we measured weight and height and administered questionnaires, including demographics, breastfeeding, Edinburgh Postnatal Depression Scale, sleep, Harvard Food Frequency, and the International Physical Activity Questionnaire. We modeled the odds of 75% loss of gestational weight gain at the study visit using multivariable logistic regression models and selected the model with the lowest Akaike information criterion (AIC) as our final model. Analyses were conducted using JMP 10–13 Pro (SAS Institute Inc.) Results: Seventy-five women with recent GDM were included in the study. The mean age of study participants was 33 (SD ±5) years old, of whom 57% were white, 30% were African American, and 20% of the women identified as Hispanic. The mean prepregnancy BMI was 31.4 kg/m 2 (SD ±5.6) and the mean pregnancy weight gain was 12.5 kg (SD ±7.8). Fifty-two percent of participants lost at least 75% of their pregnancy weight gain by the early postpartum study visit. Thirty-seven women (49%) exceeded Institute of Medicine (IOM) guidelines for gestational weight gain. In a multivariate model adjusting for weeks postpartum at the time of the study visit, less gestational weight gain (OR 0.56; 95% CI 0.39–0.73), increased age (OR 1.48; 95% CI 1.13–2.20), and lack of insulin use during pregnancy (OR 0.08 for use of insulin; 95% CI 0.00–0.73) were associated with at least 75% postpartum weight loss. Prepregnancy BMI and sleep were not retained in the model. Race/ethnicity, education, breastfeeding, nulliparity, cesarean section, depressive symptoms, dietary composition, glycemic index, and physical activity did not meet criteria for inclusion in the model. Conclusions: A substantial proportion of women with recent GDM lost at least 75% of their gestational weight gain by early postpartum. Older women, those who did not use insulin during pregnancy and those who gained less weight during pregnancy were significantly more likely to have lost 75% of gestational weight by very early postpartum.